Juridical Study on the Transfer of Shares in a Limited Liability Company That Is Decided to Be Free from All Legal Claims - Hendra Setiawan Siburian; Ali Abdullah; Fitra Deni (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
In a limited liability company, the General Meeting of Shareholders serves as the highest corporate organ authorized to determine strategic matters, including the transfer of shares. This study examines the legality of share transfer conducted without fulfilling the quorum requirements, as reflected in Surabaya District Court Decision No. 7/Pid.B/2020/PN.Sby in conjunction with Surabaya High Court Decision No. 1476/Pid/2020/PT.Sby. This research employed a normative juridical method with qualitative analysis based on statutory and case approaches. The findings indicate that such transfer is legally defective unless justified through the Circular Resolution of Shareholders mechanism. Notaries play a crucial role in ensuring legal certainty and the validity of the transaction.